2021
DOI: 10.1007/s40272-021-00442-6
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Methods Analysis of Medication Safety Incidents Reported in Neonatal and Children’s Intensive Care

Abstract: Background Critically ill neonates and paediatric patients may be at a greater risk of medication-related safety incidents than those in other clinical areas. Objective This study aimed to examine the nature of, and contributory factors associated with, medication-related safety incidents reported in neonatal and paediatric intensive care units (ICUs). Methods We carried out a mixed-methods analysis of anonymised medication safety incidents reported to the National Reporting and Learning System that involved c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…We have recently conducted a study to explore underlying contributory factors associated with medication‐related incidents reported from PICUs across England and Wales between 2010 and 2018 31 . We found that the busy and pressurised working environment of the ICU, inadequate guidelines, staffing, systems and policies were commonly involved with harmful incidents.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently conducted a study to explore underlying contributory factors associated with medication‐related incidents reported from PICUs across England and Wales between 2010 and 2018 31 . We found that the busy and pressurised working environment of the ICU, inadequate guidelines, staffing, systems and policies were commonly involved with harmful incidents.…”
Section: Discussionmentioning
confidence: 99%
“…Although AEs related to medication administration are the most frequent occurrences in health services, including NICUs and PICUs (2) , this problem was detected in a single patient in the present study. It is inferred that these events may have been underreported in the investigated units, as their identification directly depends on the quality/reliability of the information in the medical records.…”
Section: Discussionmentioning
confidence: 48%
“…On the other hand, it is believed that the low prevalence of these AEs is related to the length of professional experience and the qualification of workers for neonatal and pediatric care, as newly graduated professionals and teams not trained and not familiar with institutional safety policies were described as factors that contributed to the events arising from the use of medications (2) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between the quality of nursing care provided and its direct impact on patient outcomes has been reported in the literature. Examples include: Alghamdi et al (2021), Cannaby et al (2017), Estabrooks et al (2005), Jabbal, 2017, Kelly et al (2014), Lawton et al, 2014, McHugh et al (2013) Zwillinger and Huster (2017), West (2021).…”
Section: Introductionmentioning
confidence: 99%